Biomechanical testing of trans-humeral all-suture anchors for rotator cuff repair. (May 2019) - Aramberri-Gutiérrez, Mikel; Martínez-Menduiña, Amaia; Boyle, Simon; Valencia, Maria
Background: Rotator cuff tears are one of the most common causes of shoulder pain. All-suture anchors are increasingly being used in the arthroscopic repair of rotator cuff tears. The purpose of this experimental study is to evaluate the biomechanical properties of all-suture anchors at different insertion sites in the proximal humerus relevant to rotator cuff repairs and the remplissage procedure. Methods: Sixteen cadaveric shoulders were used for the study. Four all-suture anchors were inserted in each proximal humerus at common anchor insertion sites on the rotator cuff footprint and a simulated Hill–Sachs defect. Cyclic loading and load-to-failure tests were undertaken. The number of cycles, load to failure and nature of failure were recorded. Results: The all-suture anchors placed in the cuff footprint using a transosseous technique displayed superior biomechanical properties. Sutures sited in this way demonstrated a maximum tensile load to failure of 542 N as well as a highest mean load to failure and the maximum number of cycles before anchor failure. In descending order, all-suture anchors placed in the lateral footprint were significantly superior to those located in the medial row and in a simulated Hill–Sachs defect. Discussion: Anchors placed in the rotator cuff footprint exceeded the physiological isometric abduction forces for the supraspinatus and infraspinatus. Data obtained from our study suggest that all-suture anchors are strong enough to be used for the repair of rotator cuff tears.